2017
DOI: 10.1007/s10552-017-0896-9
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in prostate cancer risk in young HIV-positive and HIV-negative men: a prospective cohort study

Abstract: Purpose African American men have the highest incidence of prostate cancer among ethnic groups, and racial disparity is highest in younger men. Prostate cancer prevalence is rising in HIV-infected men due to improved survival on antiretroviral therapies, yet little is known about racial differences in prostate cancer risk by HIV-infection status and age. Methods Prospective cohort study of prostate cancer risk in 2800 HIV-infected and -uninfected men who have sex with men (MSM) ages 40–70 (22% African Americ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In line with previous US-based studies ( 5 , 6 , 20 ), we found lower crude prostate cancer diagnosis rates among MWH than men without HIV. However, we observed no clear overall effect of HIV on prostate cancer diagnosis rates after adjusting for potential confounders.…”
Section: Discussionsupporting
confidence: 92%
“…In line with previous US-based studies ( 5 , 6 , 20 ), we found lower crude prostate cancer diagnosis rates among MWH than men without HIV. However, we observed no clear overall effect of HIV on prostate cancer diagnosis rates after adjusting for potential confounders.…”
Section: Discussionsupporting
confidence: 92%
“…18 To date, no studies with sufficient sample size, age representation, or longitudinal followup have defined screening practices among PWH and the potential effects on cancer incidence or other factors that may limit detection. 3,5,11,12,19 As a growing number of PWH enter their fifth and sixth decades of life, opportunities for prostate cancer detection are likely to increase. Therefore, we aimed to characterize PSA screening practices among PWH and estimate standardized prostate cancer risk by HIV status while accounting for PSA testing.…”
Section: Resultsmentioning
confidence: 99%
“…Reduced opportunities for detection contributed by HIV infection should contextualize prior studies which have routinely identified lower incidence rates of prostate cancer among PWH. 3,5,11,12,19,27 Only 1 previous study, comprised predominately of younger patients, accounted for the effects of PSA testing. In that study, which included 74 incident prostate cancers, the adjusted incidence of prostate cancer remained lower for PWH.…”
Section: Discussionmentioning
confidence: 99%